Frequency of visual snow syndrome in migraine patients at tertiary care Hospital - Shakeel, Minahil; Shaheen, Manzra; Zulfiqar, Nabila; Affi, Ammara (Medical Journal of South Punjab, 2024)
Objective: To investigate the frequency of visual snow syndrome in migraine patients in a tertiary care hospital. Methodology: Study was observational, cross-sectional study conducted in the ‘Department of ophthalmology’ of Fatima Memorial Hospital and College of Medicine and Dentistry, Shadman, Lahore. The study was completed from September 2023 to December 2023 after permission from IRB. A total of 58 subjects with migraine between age group of 20 to 50 years were studied for the assessment of visual snow syndrome. Informed consent was taken and demographic data of the patients were also recorded. Clinical characteristics were collected from patients through a self-designed questionnaire. The questionnaire was based on migraine history, family history of migraine, duration of migraine, presence of visual snow and presence of additional visual symptoms such as palinopsia, enhanced entoptic phenomena, photophobia and nyctalopia. Preliminary test was performed including assessment of visual acuity. Dilated fundus examination was done to examine disc and macula. The incidence of visual snow syndrome was judged according to the proposed criteria of visual snow syndrome. Results: A total of 3 (5.2%) out of 58 subjects met the criteria for visual snow syndrome. These subjects had migraine for less than 5 years and had visual snow that last longer than 3 months and had at least two additional visual symptoms. A P-value <0.05 was considered as statistically significant. Conclusions: The study concluded that there was no statistically significant association between visual snow syndrome and migraine.